SISTEM INFORMASI PENJUALAN PADA GERAI PONSEL SURYA INDAH - Nurbaiti - (IIB Darmajaya, 2014)
If a mobile phone outlets only sell hems in quantiies so there is no problemwhich is related whit accounting report. However, if the outlet providing all the hems in full and in a large quantity, it so will have difficulty in the process of provide profit and loss. Thus the need for a system that can resolve the issue. This study will be made through an application system that is able to provide the reports required by the owner of the phone booth’s report related to inventory and financial statements. From the results of this research can be concluded, that the system can knowing the accurate and fast, and the system can determine the remaining stock of existing items.Keywords :Information Systems, phone booth, Reports.